30 Arc-Second Historical and Future Scenario Climate Surfaces for Western Honduras - Llanos Herrera, Lizeth; Navarro Racines, Carlos Eduardo; Valencia Gómez, Jefferson; Monserrate Rojas, Fredy Alexander; Vallejo Quintero, Marcela Alejandra (International Center for Tropical Agriculture, 2017)
In order to characterize the historical climate for the Western Honduras region, it was developed monthly surfaces by years through spatial interpolation and available records of weather stations. The interpolated surfaces were generated at 1-km of spatial resolution (30 arc-seconds) for monthly precipitation (1981-2015), and minimum and maximum temperature (1990-2014). It was followed the method described by Hijmans et al. (2005), using data from: (1) the DGRH (General Direction of Water Resources of the Honduran Ministry of Natural Resources); (2) the National Oceanic and Atmospheric Administration (NOAA), including data from the Global Historical Climatology Network (GHCN) and the Global Surface Summary of the Day (GSOD); and (3) the ENEE (National Electric Power Company of Honduras). In some areas with low weather station density, it was added pseudo-stations from CFSR (Climate Forecast System Reanalysis) for temperature (Ruane et al., 2015) and CHIRPS (Climate Hazards Group InfraRed Precipitation with Station; Funk et al., 2015) for precipitation. For future climates, it was performed a statistical downscaling (delta method or change factor) process based on the sum of the anomalies of GCMs (General Circulation Models), to the high resolution baseline surface (the 20-yr normal) at monthly scale (Ramirez & Jarvis, 2010). It was used data from ~20 GCMs from the IPCC AR5 (CMIP5 Archive) run across two Representative Concentration Pathways (RCP 2.6 and 8.5), for the reported IPCC future 20-year periods (IPCC, 2013): 2026-2045 (2030s) and 2046-2065 (2050s).